Urinary-derived extracellular vesicles reveal a distinct microRNA signature associated with the development and progression of Fabry nephropathy - Levstek, Tina; Vujkovac, Bojan; Cokan Vujkovac, Andreja; Trebušak Podkrajšek, Katarina (Frontiers in Medicine, 2023)
Introduction Early initiation is essential for successful treatment of Fabry disease, but sensitive and noninvasive biomarkers of Fabry nephropathy are lacking. Urinary extracellular vesicles (uEVs) represent a promising source of biomarkers of kidney involvement. Among them, microRNAs (miRNAs) are important post-transcriptional regulators of gene expression that contribute to the development and progression of various kidney diseases. We aimed to identify uEV-derived miRNAs involved in the development and/or progression of Fabry nephropathy. Methods Patients with genetically confirmed Fabry disease and matched control subjects were included. EVs were isolated from the second morning urine by size exclusion chromatography, from which miRNAs were extracted. miRNA urine exosome PCR panels were used to characterize the miRNA signature in a discovery cohort. Individual qPCRs were performed on a validation cohort that included chronological samples. We identified the target genes of dysregulated miRNAs and searched for potential hub genes. Enrichment analyses were performed to identify their potential function. Results The expression of miR-21-5p and miR-222-3p was significantly higher in patients with stable renal function and those with progressive nephropathy compared with the corresponding controls. In addition, the expression of miR-30a-5p, miR-10b-5p, and miR-204-5p was significantly lower in patients with progressive nephropathy, however, in the chronological samples, this was only confirmed for miR-204-5p. Some of the identified hub genes controlled by the dysregulated miRNAs have been associated with kidney impairment in other kidney diseases. Conclusion The miRNA cargo in uEVs changes with the development and progression of Fabry nephropathy and, therefore, represents a potential biomarker that may provide a new option to prevent or attenuate the progression of nephropathy. Furthermore, dysregulated miRNAs were shown to be potentially associated with pathophysiological pathways in the kidney.